Facilitating early diagnosis of lung cancer amongst primary care patients: the views of GPs - Wagland, R.; Brindle, L.; James, E.; Moore, M.; Esqueda, A.I.; Corner, Jessica (Wiley, 2017)
Early diagnosis of lung cancer (LC) is a policy priority. However, symptoms are vague, associated with other morbidities, and frequently unrecognised by both patients and general practitioners (GPs). This qualitative study, part of a larger mixed methods study, explored GP views regarding the potential for early diagnosis of LC within primary care. Five focus group discussions (FGDs) were conducted with GPs (n = 16) at primary care practices (n = 5) across four counties in south England. FGDs were audio-recorded, transcribed verbatim and analysed using a framework approach. Four broad themes emerged: patients’ reporting of symptoms; GP response to symptoms; investigating LC, and; potential initiatives for early diagnosis. GPs reported they often required high levels of suspicion to refer patients on to specialist respiratory consultations, and concerns of ‘system overload’ were prevalent. Greater access to more sensitive diagnostic investigations such as computed tomography, was argued for by some, particularly for symptomatic patients with negative chest X-rays. GPs challenged current approaches to promoting earlier diagnosis through national symptom awareness campaigns, arguing instead that interventions targeted at high-risk individuals might be more effective without burdening services already under pressure. Further work is needed to identify primary care patients who might most benefit from such targeted interventions.